Pengaruh Kecerdasan Emosional Dan Kemandirian Belajar Terhadap Hasil Belajar Siswa Di Sekolah Minggu Buddha (SMB) Chong De Se-Sumatera Utara - Sherly Sherly; Muljadi; Situ Asih (Dhammavicaya : Jurnal Pengkajian Dhamma, 2023)
The purpose of this study was to determine the effect of emotional intelligence and learning independence on the learning outcomes of students in Chong-De Buddhist Sunday School (SMB) throughout North Sumatra. The independent variables in this study are emotional intelligence (X1) and learning independence (X2), and the dependent variable is learning outcomes (Y). In this research, the researcher used quantitative descriptive method. The population of this study was 325 students, the researcher took 179 students as a sample. This study uses primary data, data is collected by distributing questionnaires to respondents via google forms. Testing the research hypothesis using SPSS 20.0 by testing the normality of the hypothesis, the significance, and the regression equation. The analysis method used is by using linear regression analysis and multiple correlation. The result of this study indicates that there is an effect of emotional intelligence on students’ learning outcomes with a correlation coefficient score of ry1 = 0,880. Learning independence has a positive effect on students’ learning outcomes with a correlation coefficient score of ry2 = 0.884. Emotional intelligence (X1) and learning independence (X2) have a positive and significant effect on Buddhist Sunday School (SMB) Chong-De North Sumatra students’ learning outcomes (Y) with a correlation coefficient score of ry1,2 = 0.905. This shows that emotional intelligence and learning independence have a significant impact with learning outcomes.